PENGARUH MEDIA BIG BOOK TERHADAP KEMAMPUAN LITERASI AWAL ANAK USIA 5-6 TAHUN DI KECAMATAN CIBALIUNG - Novitasari Novitasari; Alis Triena Permanasari; Tri Sayekti (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2018)
Literacy of early childhood is a capability possessed by children related to the ability to read and write. One way to stimulate children’s early literacy is to use big book media. This study used descriptive study with cross sectional approach. Sampling technique used was multi stage sampling that is cluster sampling technique, proportionate sampling, and random sampling with samples of 56 children aged 5-6 years in 4 PAUD institutions in Cibaliung Sub district. Technique of collecting data through survey. Data analysis technique using Spearman Rank bivariate analysis (rs). The results showed the correlation coefficient between big book media with initial literacy ability of (rs) 0,828. Hypothesis testing obtained t count equal to 2.057> t table of 2.00488 and obtained the coefficient of determination of 0.685. So it can be concluded that there is a positive and significant influence between the big book media on the ability of early literacy of children aged 5-6 years at early childhood institutions in Cibaliung District. Big influence given big book media on initial literacy ability equal to 68,5%.